Development of Virtual Reality (VR) Media on Ecosystem and Environmental Materials Using the Problem Based Learning (PBL) Model to Improve Digital Literacy and Critical Thinking Skills in Biology Education Students - Satriya, Robby Nur; Sari, Murni Sapta; Munzil, Munzil (BIOEDUKASI, 2024)
This research was conducted at PGRI Argopuro University Jember to determine students' digital and critical thinking abilities using VR learning media. The learning model used in this research is problem-based learning in ecology courses. This research aims to explore the potential of VR learning media to answer the challenges of 21st century skills, namely digital skills and critical thinking skills, as well as providing innovative learning designs to universities. Media applications use ADDIE. Before being given treatment, respondents will fill out a digital skills pretest questionnaire and critical thinking skills pretest. The results of survey activities and Question Validation are valid, so you can distribute the survey and questions to your respondents. Validation activities carried out by material experts are 100% in the "very effective" category. In the validation carried out by two media experts, an average score of 92.27% was obtained, so it was included in the "very effective" category. Achieved a score of 96.67% (very practical) on media practicality criteria according to education experts. Students scored an average of 85.99% on the practical test, placing them in the “very practical” category. The results of the evaluation of the implementation of the activities showed that there were differences and increases in digital literacy and critical thinking skills between students in the experimental and control classes.